Westonci.ca offers fast, accurate answers to your questions. Join our community and get the insights you need now. Connect with a community of experts ready to provide precise solutions to your questions on our user-friendly Q&A platform. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.
Sagot :
[tex]A=(x_1,y_1)\ \ \ and\ \ \ B=(x_2,y_2)\\\\|AB|= \sqrt{(x_1-x_2)^2+(y_1-y_2)^2} =\\\\= \sqrt{[-(x_2-x_2)]^2+[-(y_2-y_1)]^2}=\\\\ =\sqrt{(x_2-x_2)^2+(y_2-y_1)^2}=|BA|[/tex]
[tex]P(x_1;\ y_1);\ Q(x_2;\ y_2)\\\\|PQ|=\sqrt{(x_2-x_1)^2+(y_2-y_1)^2}\\\\|QP|=\sqrt{(x_1-x_2)^2+(y_1-y_2)^2}=\sqrt{[-1(x_2-x_1)]^2+[-1(y_2-y_1)]^2}\\\\=\sqrt{(-1)^2(x_2-x_1)^2+(-1)^2(y_2-y_1)^2}=\sqrt{(x_2-x_1)^2+(y_2-y_1)^2}\\\\|PQ|=|QP|[/tex]
We appreciate your time. Please come back anytime for the latest information and answers to your questions. We appreciate your time. Please come back anytime for the latest information and answers to your questions. Thank you for visiting Westonci.ca, your go-to source for reliable answers. Come back soon for more expert insights.